Occult Spinal Dysraphism: Case Report - Franco-Chávez, Janina; Méndez González, Nathalia Belén; Ucedo, Oscar (Medicina Clínica y Social, 2021)
Occult spinal dysraphism includes alterations in the fusion of the neural tube, in which the lesion is covered by the epidermis, its estimated incidence is 0.5 to 5 cases per 1000 live births. Cutaneous stigmata may be the only sign of pathology, which may not be very obvious. Case report of a 36-year-old woman who came to the clinic for insidious onset lumbar pain, lasting 3 weeks, which intensified over the days, radiating to the lower limbs, partially subsided with common analgesics and accompanied by paresthesias in both limbs. CT and MRI are requested, revealing sacrococcygeal anatomical abnormality characterized by spinal canal opening, absence of coccyx, low location of the medullary cone, syringomyelia, and hyperintensity at the level of the terminal filum suggestive of lipoma. The diagnosis of occult spina bifida at the sacral level was confirmed, with a lipoma of the terminal filum, an anchored cord with a low location of the medullary cone and associated syringomyelia. Currently, the benefit of prophylactic surgery in asymptomatic patients is controversial, being preferable a conservative behavior with close urological and neurological monitoring, among the prevention measures it is recommended to avoid strenuous physical exercise, reduce lumbar spine load and postural reeducation.